2011
DOI: 10.5588/ijtld.10.0498
|View full text |Cite
|
Sign up to set email alerts
|

Attributable mortality of ventilator-associated pneumonia: a meta-analysis

Abstract: Presence, compared to absence, of VAP seems to be associated with higher mortality in critically ill patients. Appropriateness of initial antimicrobial treatment in such patients may moderate this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 60 publications
3
23
0
Order By: Relevance
“…In this context, A . baumannii VAP has been associated to higher mortality and longer LOS in ICU than VAP caused by other pathogens [21, 2628]. For instance, in a cohort of 163 patients with VAP, A .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, A . baumannii VAP has been associated to higher mortality and longer LOS in ICU than VAP caused by other pathogens [21, 2628]. For instance, in a cohort of 163 patients with VAP, A .…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis on 24,186 patients from 44 observational studies [28] found that VAP was associated with higher mortality (OR 1.96, 95%CI 1.26–3.04) than their comparative groups; notwithstanding, this association was not found in VAP patients with appropriate initial treatment. The higher mortality of VAP caused by more resistant strains is probably related to the less likelihood of receiving appropriate therapy [21].…”
Section: Discussionmentioning
confidence: 99%
“…espiratory tract infections caused by multidrug-resistant (MDR) bacteria, in particular Pseudomonas aeruginosa, are difficult to treat and often associated with high rates of recurrence, mortality, and morbidity (1)(2)(3). For respiratory infections caused by MDR P. aeruginosa, inhalational and intravenous colistin (polymyxin E) is often the only effective option (4,5).…”
mentioning
confidence: 99%
“…11 A meta-analysis found that the average attributable mortality to VAP is 32.5% in the ICU, 12 supported by another study 13 that found 33%. VAP increases the ICU and hospital length of stay, as well as the time the patient requires ventilatory support.…”
Section: Introductionmentioning
confidence: 81%